Hepatitis B Virus Infection and Its Determinants among Pregnant Women in Ethiopia: A Systematic Review and Meta-Analysis - Alemu, Addisu Alehegn (Infect Dis Obstet Gynecol, 2020)
BACKGROUND: Hepatitis B virus (HBV) is an infectious and a global public health problem. The prevalence of HBV infection among pregnant women is between 2.3% and 7.9%. HBV infection during pregnancy is associated with prenatal transmission to the fetus. HBV has an effective vaccine which reduces up to 96% of the transmission. Although different studies were conducted in Ethiopia, none of them showed the national prevalence of HBV infection among pregnant women. Therefore, this study was conducted to determine the pooled prevalence of HBV and its associated factors in Ethiopia. METHODS: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for articles. All observational published studies were retrieved using relevant search terms in Google Scholar, African Online Journal, CINAHL, and PubMed databases. Newcastle-Ottawa assessment checklist for observational studies was used for critical appraisal of the included articles. The meta-analysis was done with STATA version 14 software. The I(2) statistics were used to test heterogeneity whereas Begg's and Egger's tests were used to assess publication bias. Odds ratio (OR) with a 95% confidence interval (CI) was presented using the forest plot. RESULTS: A total of twenty-three studies were included in this systematic review and meta-analysis. The pooled prevalence of HBV in Ethiopia was 4.75% (95% CI: 4.06, 5.44). The subgroup analysis showed a higher prevalence of HBV infection among pregnant women in Gambella (7.9%) and the lowest in Southern Nations, Nationalities, and Peoples' Region (SNNPR) (2.3%). Associated factors with HBV infection include history of multiple sexual partner (OR = 6.02 (95%CI = 3.86, 9.36)), blood transfusion history (OR = 5.71 (95%CI = 3.25, 10.04)), abortion history (OR = 3.58 (95%CI = 2.10, 6.09)), and history of body tattoo (OR = 2.83 (95%CI = 1.55, 5.17)). CONCLUSIONS: HBV infection among pregnant women is a common public health problem in Ethiopia. Multiple sexual partners, abortion history, blood transfusion history, and body tattoo were significantly associated with HBV infection. Policies and strategies should focus on factors identified in this study to improve the prevention of HBV among pregnant women.